Innovation in planning: creating and securing public value. Issue 3 (3rd March 2020) - Vigar, Geoff; Cowie, Paul; Healey, Patsy
ABSTRACT: Innovation is a much hyped term and yet is difficult to define. In planning, this difficulty is partly explained by the 'wicked' nature of many planning problems and the complexities of evaluating diverse, often long-term cultural, social and environmental outcomes; but also because innovation is often associated with the economic. Explicitly expanding the concept of innovation to foreground non-financial outcomes helps the planning discipline understand the complex ways planning actions make novel, positive contributions to societal goals. An idea of public value helps evaluate how innovation in spatial planning provides benefits beyond private individuals. The concept is mobilized to test a framework of innovation in planning that underpins an empirical review. The framework and the wider review highlights five features present in innovative planning that delivers public value.